Efektivitas Layanan Perpustakaan Berbasis Inklusi Sosial di Perpustakaan Umum Daerah Kota Payakumbuh - Erlin, Ifany Putri; Nelisa, Malta (TSAQOFAH, 2025)
This study aims to describe the services and effectiveness of the social inclusion-based library program at the Regional Public Library of Payakumbuh City. The research used a quantitative approach with saturation sampling techniques, involving 65 respondents who participated in social inclusion activities in 2024. The main instrument was a questionnaire that had been tested for validity and reliability. The results indicate that social inclusion services achieved a score of 1625 out of 5980 (93%), which falls into the "very good" category. These services include the provision of diverse collections, collaboration with local institutions, as well as routine training based on social inclusion. The effectiveness of the program achieved a score of 1040 out of 4420 (81%), also in the "very good" category. The program was deemed successful in empowering women, youth, and micro-entrepreneurs through skill enhancement and access to information. Active socialization and consistent program monitoring contributed to the achievement of the program's inclusive objectives. These findings affirm the important role of libraries in community empowerment.